Redefining urban and suburban America. evidence from Census 2000 - Katz, Bruce; Lang, Robert, 1959-; Berube, Alan (James A. Johnson metro series., 2005)
"Probes trends in migration, income and poverty, and housing in the nation's largest cities and metropolitan areas, using data from the long form of the 2000 census"--Provided by publisher